(untitled) - Rose, Karen; 1964- (New York , New York, 2021)
For decades, Eden has remained hidden in the remote wilds of the Pacific Northwest, with Pastor keeping his cults followers in thrall for his personal profit and sexual pleasures. But the Founding Elders are splintering, and Pastors surrogate son, DJ, is scheming to make it all his own. When two of Edens newest members send out a cry for help, it reaches FBI special agent Tom Hunter, whose friend and fellow FBI special agent Gideon Reynolds and his sister, Mercy, are themselves escapees of the Eden cult, their lives in danger from the Founding Elders who want them silenced forever. The three have vowed to find the cult and bring it down, and now, they finally have a solid lead. Neutralizing Edens threat will ensure Toms new friends can live without fear and will save those who are being held there against their will. But his own fear spikes when his best friend, ex-Army combat medic Liza Barkley, joins the case, putting her life--and their blossoming love--in danger. With everything they hold dear in the balance, Tom and Liza, together with Gideon and Mercy, must end Eden once and for all.
Keywords: Federal Bureau of Investigation; Officials and employees; Fiction; United States; Fiction; Criminal investigation; Fiction; Ex-cultists; Fiction; Brothers and sisters; Northwest, Pacific; Fiction; Cults; California; Fiction; Northwest, Pacific; Fiction